2007
DOI: 10.1002/chem.200700364
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐Transfer Emission Involving Three‐Coordinate Organoboron: V‐Shape versus U‐Shape and Impact of the Spacer on Dual Emission and Fluorescent Sensing

Abstract: New V-shaped bifunctional organosilicon compounds that contain an electron acceptor, B(Mes)2, and an electron donor, N(1-naph)Ph, with the formulae Ph2Si{p-C6H4B(Mes)2}{p-C6H4N(1-naph)ph)} (1), Ph2Si{p-C6H4(Mes)2}{p-biphenyl-N(1-naph)ph} (2), and Si{p-C6H4B(Mes)2}2{p-C6H4N(1-naph)ph)}2 (3) have been synthesized as model compounds for the investigation of through-space charge-transfer emission involving triarylboron and triarylamino centers. The photophysical properties of the new bifunctional organosilicon com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
83
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 50 publications
12
83
1
Order By: Relevance
“…The bromo-substituted groups in 5 and 6 didn't have contribution to the HOMO or LUMO orbitals. The results also indicated that the tetrahedral silicon core does not have significant effect on the electronic properties of 1e6, which is consistent with previous reports [6,7]. It is noteworthy that these compounds all have a deep energy gap with the range from 4.9585 eV (6) to 5.1879 eV (1).…”
Section: Compoundsupporting
confidence: 91%
“…The bromo-substituted groups in 5 and 6 didn't have contribution to the HOMO or LUMO orbitals. The results also indicated that the tetrahedral silicon core does not have significant effect on the electronic properties of 1e6, which is consistent with previous reports [6,7]. It is noteworthy that these compounds all have a deep energy gap with the range from 4.9585 eV (6) to 5.1879 eV (1).…”
Section: Compoundsupporting
confidence: 91%
“…Gabbaï and coworkers have made excellent progress of chelating a fluoride anion by combining dimesitylboryl and another F − sensitive group [14][15][16][17][18][19]. Wang and co-workers also demonstrated their results of F − sensing fluorescent borane based on different charge-transfer emission from B--N derivatives [20][21][22]. The F − bonding action by triarylborane-functionalized polystyrene was also found by Jäkle et al [23].…”
Section: Introductionmentioning
confidence: 63%
“…Recently, several research groups have reported that trivalent boron compounds can be used as effective colorimetric, fluorescent, or ratiometric sensors for the detection of fluoride by utilizing the empty p orbital on the boron center [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Yamaguchi et al firstly reported the colorimetric fluoride ion sensing of triarylboron [11][12][13].…”
Section: Introductionmentioning
confidence: 98%
“…[29]). Figure 8) [30]. The emission color of these compounds changed evidently after addition of F  , which was attributed to the dual fluorescent emission.…”
Section: Fluoride Detection In Organic Mediamentioning
confidence: 92%